Determine the exact length of the veneers through programming the condylar inclination of the semi-adjustable articulator - Del Valle Lovato, Juan; Balcazar, Jorge (Odontología, 2024)
Purpose: Various aspects of veneers have been described in literature, such as preparation, material, manufacturing method, bonding technique, remaining dental structure color, among others. The length of veneers incisal edge, that has been determined through photos or videos doing a functional evaluation, creating an anterior guide by mockup in addition to the diagnostic elements mentioned above, the veneers were exactly length based on the condyle inclination. Materials and methods: The technique shown in the following clinical case report, aims to customize the length of the veneers by programming the condylar inclination and the incisal plate of the semi-adjustable articulator. Results: The veneers made with the present technique was accurately. Conclusion: Customize the length of the veneers demonstrated avoid wear, fracture or breakdown of the bond.